Suspended particulates at the Point Loma, California wastewater outfall - Stokes, M. Dale; Leichter, James J.; Nadeau, David (Frontiers in Marine Science, 2023)
A recent study conducted at the Point Loma wastewater outfall in San Diego used a novel sampling technique, the Pelagic Laser Tomographer (PLT), in combination with traditional water column profiling instruments to analyze suspended particulate distributions and effluent plume dynamics. Coastal wastewater discharges create buoyant plumes that interact with the surrounding water, and the tracking and mapping of the resulting diluted effluent is essential for monitoring outfall system performance. The results from the PLT sampling highlight the utility of high spatial and temporal resolution estimates of suspended particulate size spectra to help capture the dynamics of the plume interactions with the coastal current flow field. In addition, new tools like the PLT can help marine scientists estimate natural and anthropogenic particulate size distributions that are essential to our understanding sediment and pollutant transport, nutrient cycling, and ecosystem energy dynamics.